Analysis of the Implementation of the Zoning System in New Student Admissions in High School - Putra, Endri; Kosim, M.; Nirwana, Herman; Fikri, Miftahul; Triawan, Fandy; Yuliartati, Yuliartati; Saputra, Adi; Heriyanto, Helmi (AT-TA'LIM, 2025)
Various problems that arise are caused by the school quality zoning system policy, low student learning motivation, and low student competence. The purpose of this study is to analyse the problems/inhibiting factors of the zoning system. This study uses the sequential mixed methods method, especially the sequential explanatory strategy. Based on the results of the study, it was found that the advantages of the zoning system are cheaper, such as cheaper student transportation costs to school, no discrimination against favourite schools, and encouraging teachers to be more creative in designing learning that is in accordance with student conditions, while the problems and supporters of the implementation of the zoning system in accepting new students. Some implications and recommendations obtained from this study. First, for the central government, considering that the competition for prospective students with the zoning system is getting tighter, the Central Government must adjust the existing provisions by reducing the percentage of the zoning system path and increasing the percentage of the achievement path. Second, the Provincial Government in determining the zone does not only refer to the distance between home and school but also needs to optimize the involvement of community leaders in determining the zone of each school.